Changes to the Bacterial Microbiome in the Rhizosphere and Root Endosphere of Persea americana (Avocado) Treated With Organic Mulch and a Silicate-Based Mulch or Phosphite, and Infested With Phytophthora cinnamomi - Farooq, Qurrat Ul Ain; Hardy, Giles Edward St. John; McComb, Jen A.; Thomson, Peter Campbell; Burgess, Treena Isobel (Frontiers in Microbiology, 2022)
Plant growth and responses of the microbial profile of the rhizosphere soil and root endosphere were investigated for avocado plants infested or not infested with Phytophthora cinnamomi and the changes were compared in plants grown with various soil additives or by spraying plants with phosphite. Soil treatments were organic mulches or silica-based mineral mulch. Reduction of root growth and visible root damage was least in the infested plants treated with phosphite or mineral mulch applied to the soil. Rhizosphere soils and root endospheres were analyzed for bacterial communities using metabarcoding. Bacterial abundance and diversity were reduced in infested rhizospheres and root endospheres. The presence or absence of mineral mulch resulted in greater diversity and larger differences in rhizosphere community composition between infested and non-infested pots than any other treatment. Some rhizosphere bacterial groups, especially Actinobacteria and Proteobacteria, had significantly higher relative abundance in the presence of Phytophthora. The bacterial communities of root endospheres were lower in abundance than rhizosphere communities and not affected by soil treatments or phosphite but increased in abundance after infection with P. cinnamomi. These findings suggested that the addition of silicate-based mineral mulch protects against Phytophthora root rot, which may be partly mediated through changes in rhizosphere bacterial community composition. However, the changes to the microbiome induced by spraying plants with phosphite are different from those resulting from the application of mineral mulch to the soil.